Role of Medicinal Plants in the Prevention of Covid-19 Pandemic (Medico Legal Update, 2020)
Coronavirus disease 2019 (COVID-19) is a life-threatening global health scenario. The WHO (World HealthOrganization) has announced this disease as global issue. The severity of this disease causes highest deathrates from December 2019-October 2020 world wide. There is an urgent need to develop medicines andvaccine to prevent the immune system of human. Medicinal plants and plant based drugs play a major role inpreventing by provoking the immune system. This review discusses about the major global issue pandemiccoronavirus disease (Covid -19) and the traditional medicines as preventive and curative agent in treatingthis global health issue.